Patient‐reported functional outcomes and oncological control after primary focal cryotherapy for clinically significant prostate cancer: A Phase II mandatory biopsy‐monitored study. Issue 8 (9th March 2023) - Tan, Yu G.; Law, Yan M.; Ngo, Nye T.; Khor, Li Y.; Tan, Puay H.; Ong, Enya H. W.; Yuen, John S. P.; Ho, Henry S. S.; Tuan, Jeffrey K. L.; Kanesvaran, Ravindran; Gupta, Rajan T.; Rozen, Steven; et al.
Abstract: Introduction: We report herein the impact of focal therapy (FT) on multi‐domain functional outcomes in a Phase II prospective clinical trial (NCT04138914) in focal cryotherapy for clinically significant prostate cancer (csPCa). Methods: The primary outcome was the detection of a ≥5 point deterioration in any of the four main expanded prostate index composite (EPIC) functional domains. Pretreatment multiparametric magnetic resonance imaging (mpMRI) and transperineal targeted and systematic saturation biopsy were used to select patients with prostate‐specific antigen (PSA)≤20 ng/mL, Gleason grade group (GG) ≤4, mpMRI lesion volume ≤ 3 mL (for a single lesion) or ≤1.5 mL (where two lesions were present). Focal cryotherapy was performed with a minimum 5 mm margin around each target lesion. EPIC scores were obtained at baseline and posttreatment at 1, 3, 6, and 12 months. Mandatory repeat mpMRI and prostate biopsy were performed at 12 months to determine the infield and outfield recurrence. Results: Twenty‐eight patients were recruited. The mean age was 68 years, with PSA of 7.3 ng/mL and PSA density of 0.19 ng/mL 2 . No Clavien–Dindo ≥3 complications occurred. Transient worsening of EPIC urinary (mean diff 16.0, p  < 0.001, 95% confidence interval [CI]: 8.8–23.6) and sexual function scores (mean diff 11.0, p :0.005, 95% CI: 4.0–17.7) were observed at 1‐month posttreatment, with recovery by Month 3. A subgroup who had ablation extending to the neurovascular bundle had a trend to delayed recovery of sexual function to Month 6. At 12‐month repeat mpMRI and biopsy, 22 patients (78.6%) had no detectable csPCa. Of the six patients (21.4%) who had csPCa recurrences, four were GG2, one GG3, and one GG4. Four patients underwent repeat FT, one underwent radical prostatectomy, while the remaining one patient with low‐volume GG2 cancer opted for active surveillance. Conclusion: FT using cryotherapy was associated with a transient deterioration of urinary and sexual function with resolution at 3 months posttreatment and with reasonable early efficacy in well‐selected csPCa patients.